The Legal Protection of Debtors as Victims of Personal Data Misuse in the Use of Shopee PayLater Service - Leksi, Leksi; Sahay, Tahasak; Wulandari, Vicka Prama (Dinasti Research, 2025)
Shopee PayLater services offer convenience in transactions but also pose risks of personal data misuse, thereby underscoring the importance of legal protection under the Electronic Information and Transactions Law (ITE Law) and the Personal Data Protection Law (PDP Law) to maintain consumer trust. Shopee PayLater facilitates transactions through a